2009
DOI: 10.1097/sga.0b013e3181c10747
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Catheter-Related Bloodstream Infections in Children With Intestinal Failure

Abstract: Catheter-related bloodstream infection is a major cause of mortality and morbidity in the intestinal-failure population. This study reports characteristics of CRBSI with implications for clinical management in parenteral nutrition-dependent children with intestinal failure. The researchers report the rate of central catheter infections, and the causative organisms, as well as identify risk factors in our intestinal-failure patients that would be amenable to preventive measures.The study is a retrospective revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 23 publications
(44 reference statements)
2
30
0
Order By: Relevance
“…17 Drews et al reported seven infections per 1000 catheter-days in 45 children on PN at home over two years' follow-up. 19 In our cohort, the incidence of CRBSI was 1.3 infections per 1000 catheter-days in children receiving PN at home, at the lower end of the previously reported range.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…17 Drews et al reported seven infections per 1000 catheter-days in 45 children on PN at home over two years' follow-up. 19 In our cohort, the incidence of CRBSI was 1.3 infections per 1000 catheter-days in children receiving PN at home, at the lower end of the previously reported range.…”
Section: Discussionmentioning
confidence: 82%
“…The reported average indwelling time for CVC in children with PN at home was between 244 and 780 days. 17,19,32 This study has a number of limitations: the sample size is small and we collected only one year of patients' data. We do not have a control group; to compare our findings we used the previously published incidence of CRBSI.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pediatric patients with short gut syndrome, who are dependent upon parenteral nutrition, are at high risk for recurrent central line infections and thus may have higher cumulative antibiotic exposure than even some critical care and oncology patients. [34][35][36][37] For such patients, pathogens causing CLABSIs may be more likely to be antibiotic resistant. Other potential explanations include differences in infection control practices or opportunities for transmission in pediatric ward locations compared to critical care or oncology locations.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, utilization of PN is associated with a high incidence of catheter-associated bloodstream infections (CA-BSI). [13][14][15] The incidence of Background: Home parenteral nutrition (HPN) is lifesaving for children with intestinal failure. Catheter-associated bloodstream infections (CA-BSI) are common in hospitalized patients receiving parenteral nutrition (PN), but data evaluating CA-BSI in children receiving HPN are limited.…”
Section: Introductionmentioning
confidence: 99%